STRENGTHENING CAMPUS IMPACT THROUGH PHYSICS LABORATORY INTERNSHIP PROGRAM IN SCHOOLS IN OPTIMIZING STUDENTS' SCIENTIFIC ATTITUDES - Sri Jumini; Nur Chasanah Suryani; Hamzah; Nugroho Prasetya Adi; Riana Susanti; Hidayat (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
Students' scientific attitudes remain a problem in science learning, including physics. Frequently encountered problems include low curiosity, lack of thoroughness in conducting experiments, weak critical thinking skills regarding data, and a lack of objectivity in drawing conclusions. This study aims to describe students' scientific attitudes in a laboratory internship program at school to strengthen impactful campuses. The study used a descriptive quantitative approach. Data collection techniques used questionnaires and observation methods. Data analysis was conducted using descriptive statistics. The results showed that attitudes of honesty, thoroughness, discipline, responsibility, curiosity, cooperation, and communication were in the range of 51%–75%, in the good category. The results of this study provide a real contribution to the role of higher education in strengthening the role of impactful campuses through a physics laboratory internship program at school, which emphasizes meaningful, relevant, and socially-contributing learning. This program also provides real-life experience in optimizing students' scientific attitudes.